Linkage to care of HbsAg-positive and anti-HCV-positive patients after a systematic screening approach in the German primary care setting. Issue 3 (March 2018) - Lüllau, Anja; Petroff, David; Bätz, Olaf; Kramer, Jan; Jedrysiak, Katrin; Tenckhoff, Hannelore; Berg, Thomas; Wolffram, Ingmar; Wiegand, Johannes
Abstract : Background: Identification of previously unknown cases is important to lower the burden of chronic hepatitis B and C infection. However, a screening program in the primary care setting has not yet been established. Therefore, a systematic screening project was conducted in 21 008 patients (Wolffram and colleagues). Here, we describe linkage to care of identified HbsAg-positive and anti-hepatitis C virus (HCV)-positive patients. Methods: General practitioners characterized further medical care by a standardized questionnaire. Data of 48/110 HbsAg-positive and 114/199 anti-HCV-positive patients were available. An APRI index more than 2 or up to 0.5 indicated the presence of cirrhosis or the absence of fibrosis. Results: APRI was calculated in 32/48 hepatitis B virus (HBV) patients (>2: n =1; ⩽0.5: n =29) and 34/114 HCV patients (>2: n =4; ⩽0.5: n =23). The general practitioners were already aware of the positive HBsAg and anti-HCV-test in 13/48 and 59/114 patients, respectively. For 29/35 newly diagnosed HBV patients and 26/55 HCV patients, further diagnostics were initiated: ultrasound 77 versus 38%, liver biopsy 20 versus 4%, and gastroscopy 20 versus 7%. Antiviral treatment was initiated in 5/35 HBV cases and in 10/55 HCV patients. A family screening was initiated in 22/35 HBV versus 13/55 HCV index patients and showed one additional HbsAg-positive and two anti-HCV-positive cases. Diagnostic procedures differed significantly between anti-HCV-positive and HbsAg-positive patients ( P <0.001 for APRI, ultrasound, and family screening; P =0.03 for liver biopsy). Conclusion: Diagnostic procedures should be improved for hepatitis C-infected patients. The APRI index was only of limited value in the primary care setting.